Penguatan Keterampilan Berbicara Bahasa Inggris melalui Program English Speaking Club berbasis Produksi Konten Digital di SMA Ahmad Yani 2 Baureno - Anita Dwi Hapsari; Buyun Khulel; Belgis Raya Bian Paradieshta; Aprilia Sri Wulandari (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2026)
Speaking proficiency remains a significant challenge for secondary school students due to limited vocabulary mastery, low self-confidence, and insufficient opportunities for authentic oral practice. This article reports the implementation of an English Speaking Club program designed through a project-based approach to strengthen students’ speaking competence through gradual digital content production over four weeks. The program employed a descriptive qualitative framework involving classroom observation, guided mentoring sessions, and analysis of students’ outputs in the form of videos and podcasts. The instructional sequence was progressively structured, covering self-introduction and daily activities, hobbies and future career aspirations, school description in a podcast format, and storytelling performance. The findings indicate observable improvement in fluency, pronunciation clarity, confidence in public performance, organization of ideas, and expressive delivery. The transformation extended beyond linguistic development to include affective growth, particularly in students’ willingness to communicate spontaneously. The content-production-based approach fostered active participation and created meaningful learning experiences by positioning students as producers of authentic communicative performances. This program demonstrates potential as an alternative model for contextual and practice-oriented speaking instruction aimed at sustaining communicative competence development in secondary education settings.